Deformation based seismic design of pile supported marine facilities - Polat, Şamil Şeref. (Thesis (Ph.D.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2008., 2008)
Pile supported marine structures with batter piles comprise a considerable share in the modern marine structure stock built in seismic zones. Their stiff nature offers significant advantages to structural engineers in resisting non-seismic loads such as, berthing, mooring etc. On the other hand the poor performance of marine structures supported by batter piles in recent earthquakes has revealed certain disadvantages of these systems in resisting seismic loads. The general design approach for pile supported marine structures is to ensure that the cap-beam and the deck system will remain elastic and the yielding will occur either at the pile-to-cap beam connection or along the pile itself. Traditionally those structures were designed with force-based design methods to withstand seismic forces reduced by response modification factors or to a force equal to a fraction of the total weight of the structure. The past research in last decade have shown that the poor behavior of batter piles is mainly related to this force-based approach, which lack to identify the problems associated to post-yield behavior of these piles. When batter piles yield in tension, either in the form of pile-to-cap-beam connection or pile pull-out of soil pile-cap starts to pole vault over the compression piles as the structure deforms laterally. As the structure rises, substantial tension forces are developed both in the vertical and orthogonal batter piles and create additional shear and moment to the cap-beam. The non-linear analysis performed on generic pier frames in this study revealed that substantial amplifications in section forces have been observed at the pile-cap with decrease in strength and increase in batter. Even though section compactness is a well known requirement in steel design most of the modern marine structure design codes does not provide a compactness criteria. When the connection of the tension batter pile is designed to develop high axial forces, the compression piles with non-compact steel section have a tendency to yield under the action of earthquake induced bending moments and high compression forces at the pile-soil interface. The inelastic response history analysis performed on generic pier frames indicate formation of inelastic local buckling on compression piles results in partial or total collapse of the structure. Design recommendations are provided based on the results of the performed nonlinear analysis.
Keywords: Piling (Civil engineering) -- Design and construction.; Concrete piling -- Design and construction.